2001
DOI: 10.1128/iai.69.8.5186-5188.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Antigen Exposure on Development of Immunity to Helicobacter pylori Infection in Mice

Abstract: The effect of low-dose antigen exposure on the development of immunity to Helicobacter pylori infection was studied in outbred mice. Animals that were primed with a subinfectious number of H. pylori bacteria exhibited significantly lower bacterial loads after challenge with an infectious dose of pathogen (versus controls, P < 0.05)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…We have previously used several methods for quantification of Th subsets [18,32,33] but found that flow-cytometric analysis provides more detailed information. In agreement with our data, the H. pylori SS1 wt strain elicits a Th2 response in outbred Swiss mice [34]. Several groups, however, have shown that mice usually generate a Th1 response to H. pylori [6,8,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have previously used several methods for quantification of Th subsets [18,32,33] but found that flow-cytometric analysis provides more detailed information. In agreement with our data, the H. pylori SS1 wt strain elicits a Th2 response in outbred Swiss mice [34]. Several groups, however, have shown that mice usually generate a Th1 response to H. pylori [6,8,30].…”
Section: Discussionsupporting
confidence: 90%
“…Immunized, protected mice demonstrate a Th1 response [4,6], but an increase in gastric Th2 cells has been reported, indicating that these cells may also be important [38]. Other investigators have indicated a protective role for Th1 and/or Th2 responses [34,39,40], but, since immunity can be achieved in IL-4-but not in IL-12-deficient mice [4,5], it is agreed that Th1 responses are necessary for protection. IFN-g is associated with gastritis [3,24,41], but evidence suggests that Th1 responses, and not IFN-g responses, are required for protection [6]; the mechanisms of Th1-mediated protection remain elusive.…”
Section: Discussionmentioning
confidence: 94%
“…A number of vaccine antigens have been tested over the years ranging from whole cell lysates 167,168 and sub-infectious doses of live bacteria, 169 to single or combined purified antigens including urease, 170,171 HP-NAP, 172 CagA, 173 VacA, 174 catalase, 175 heat shock proteins, 176 and lipopolysaccharide. 177 The search for new vaccine antigens that are surface exposed and highly conserved amongst diverse strains from across the world is still continuing using genomic and proteomic approaches.…”
Section: Prospects For Future Vaccinesmentioning
confidence: 99%
“…Other notable vaccination articles: animals that were primed with a subinfectious number of H. pylori bacteria exhibited significantly lower bacterial loads after challenge with an infectious dose of pathogen [28]. Kleanthous et al.…”
Section: H Pylori Vaccination and Protective Immunitymentioning
confidence: 99%
“…Other notable vaccination articles: animals that were primed with a subinfectious number of H. pylori bacteria exhibited significantly lower bacterial loads after challenge with an infectious dose of pathogen [28]. Kleanthous et al suggested that the ability to achieve sterilizing immunity in animal vaccination models may be dependent upon the challenge strain of bacteria [29].…”
Section: H Pylori Vaccination and Protective Immunitymentioning
confidence: 99%